MODERN ASSESSMENT METHODS USED BY ENGLISH TEACHERS - Ibrokhimova Latofat (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Assessment has long been a fundamental component of the educational process, serving as a means to measure student learning, inform instruction, and evaluate educational effectiveness. Traditionally, assessments focused heavily on rote memorization and summative testing, which primarily aimed to determine whether students had achieved specific learning outcomes at the end of instructional units. However, with the evolution of educational paradigms, there has been a shift towards more comprehensive and authentic assessment practices that better capture students’ skills, understanding, and competencies. Modern assessment approaches emphasize not only summative evaluation but also formative, diagnostic, and performance-based assessments, which facilitate ongoing feedback, identify learning gaps, and promote active student engagement.